A COMPARATIVE STUDY OF TWO WAYS TRANSLATION FROM ENGLISH TO INDONESIAN AND INDONESIAN TO ENGLISH AT FLDI NURUL JADID ISLAMIC INSTITUTE - Luluk Durriyatul Muhlisoh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: By aiming for natural equivalence, translation is the process of conveying the meaning and style of the source language into the target language. To translate the text perfectly, a translator needs two ways of translation as a way to know consistency in translation. This study presents a comparative study of two ways of translation from English to Indonesian and Indonesian to English. This study examines how consistent results of English texts that are translated into Indonesian and retranslated into English and investigates what version is more difficult for students when translating English to Indonesian or translating Indonesian to English. The research of this study used a mixed method and the subjects are 5 advanced-level students of FLDI Nurul Jadid Islamic Institute. The researcher used a translation test and interviews as the instrument to collect the data from the participant. The findings of this study showed both raters gave a consistent assessment of translation results based on Kappa = 0.750 with p .000. Thus, the majority of participants' perceptions revealed that translating Indonesian text into English is the most challenging or difficult aspect of translation because of difficulties in arranging and concentering word position. To minimize the threat of invalid reliability future researchers and teachers to be requested to translate Indonesian text into English using another text. keywords: Two ways Translation, Consistency, FLDI Nurul Jadid